Two‐Component Self‐Assembly: Hierarchical Formation of pH‐Switchable Supramolecular Networks by π–π Induced Aggregation of Ion Pairs. Issue 43 (16th September 2016) - Samanta, Krishnananda; Ehlers, Martin; Schmuck, Carsten
Abstract: Two‐component self‐assembly is a promising approach to construct functional nanomaterials. Interaction of a flexible guanidiniocarbonyl pyrrole tetra‐cation (1 ) with naphthalene diimide dicarboxylic acid (NDIDC) in aqueous DMSO leads to the formation of supramolecular networks. First, the carboxylate groups of NDIDC bind to the guanidiniocarbonyl pyrrole cations of1 in a 1:2 stoichiometry. Further π–π induced aggregation then leads to 3D networks, as established by dynamic light scattering studies (DLS), NMR, fluorescence titration, viscosity measurements, AFM, and TEM microscopy. Due to ion pairing, the resulting aggregates can be switched between the monomers and the aggregates reversibly using external stimuli like protonation or deprotonation. At high concentration, a stable colloidal solution is formed, which shows an extensive Tyndall effect. Increasing the concentrations even further leads to formation of a supramolecular gel. Abstract : Supramolecular networks : pH‐Switchable, cooperative two‐component supramolecular self‐assembly is described. Naphthalene diimide dicarboxylic acid (NDIDC) first forms a 2:1 ion pair with a guanidiniocarbonyl pyrrole tetra‐cation, which further aggregates into supramolecular networks through π–π interactions of the NDI cores.